2019
DOI: 10.1177/1550147719888169
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of different deep learning-based methods on fault diagnosis for geared system

Abstract: The running state of a geared transmission system affects the stability and reliability of the whole mechanical system. It will greatly reduce the maintenance cost of a mechanical system to identify the faulty state of the geared transmission system. Based on the measured gear fault vibration signals and the deep learning theory, four fault diagnosis neural network models including fast Fourier transform–deep belief network model, wavelet transform–convolutional neural network model, Hilbert-Huang transform–co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Moreover, the DBN has strong nonlinear processing ability and good discriminant ability, so that it has been widely used in the many fields, such as image processing [26], human action identification [27], natural language processing [28]. The DBN model has been preliminarily applied in bearing fault diagnosis [29][30][31] and gear fault diagnosis [29,[32][33][34] since it has been applied to aero-engine structural health identification by scholars [34], however, it has not yet been reported for the identification of fault parameters in double-rotor misalignment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the DBN has strong nonlinear processing ability and good discriminant ability, so that it has been widely used in the many fields, such as image processing [26], human action identification [27], natural language processing [28]. The DBN model has been preliminarily applied in bearing fault diagnosis [29][30][31] and gear fault diagnosis [29,[32][33][34] since it has been applied to aero-engine structural health identification by scholars [34], however, it has not yet been reported for the identification of fault parameters in double-rotor misalignment.…”
Section: Introductionmentioning
confidence: 99%
“…The fault in mechanical system is the abnormal state caused by the damage of its component, which induces the mechanical system to be dis‐functional. The fault can be monitored, recognized, and diagnosed by equipment model, running parameter, dynamic response and symptoms 1,2 . Due to the equipment's power frequency vibration, electrical noise, hydraulic system pulsation noise, and noise interference in transmission link modulation, the features in online monitoring system is weak and the feature extraction method is sensitive to the interference factors.…”
Section: Introductionmentioning
confidence: 99%
“…The fault can be monitored, recognized, and diagnosed by equipment model, running parameter, dynamic response and symptoms. 1,2 Due to the equipment's power frequency vibration, electrical noise, hydraulic system pulsation noise, and noise interference in transmission link modulation, the features in online monitoring system is weak and the feature extraction method is sensitive to the interference factors. The solution for mechanical fault diagnosis has become a hot topic in the field of mechanical design.…”
Section: Introductionmentioning
confidence: 99%
“…Vibration signal analysis involves separating the collected vibration signal from the fault characteristic signal and identifying the fault in the system by analyzing the separated signal [ 9 ]. In the last few decades, many signal-based fault diagnosis methods have been developed for fault feature identification [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the performance of fault diagnosis systems depends on the feature spaces used [ 28 ], it was observed that these feature spaces were used arbitrarily and not combined in such a way to achieve generalization between different conditions, that the bearings may be subjected. For instance, in [ 9 ] while the FFT would give unsatisfactory results with a signal whose frequency components changes with time, the wavelet transform is known to suffer from fixed scale resolution which would affect its real-life applications, and the HHT suffers from instability in its signal decomposition process.…”
Section: Introductionmentioning
confidence: 99%